A Case Study of a Writer Using Code Switching - Yayu Heryatun (Universitas Bunda Mulia, 2017)
This research is intended to find out the types of code switching that is used in short stories and to describe the reasons why a writer does code switching in her short stories. It is a case study involving a writer of short story. Three short stories as document analysis and interview served as the data collection method. The result of this research indicated that the intra-sentential type of code switching occurs mostly in her short stories, followed by inter-sentential code switching. In addition, the reasons why code switching occurs are firstly, that certain notions or concepts are simply better expressed in the other language; secondly, code switching is used as a communicative or social strategy to show speaker involvement, mark group identity, exclude someone, raise one’s status, show expertise, and so on; thirdly, it is used to refill a linguistic need for a word or an expression; and finally, the last reason is to strengthen command. Keywords: Code switching, short stories